In vitro effects of relaxin on gene expression in porcine cumulus-oocyte complexes and developing embryos - Willard Scott T; Greene Jonathan M; Feugang Jean M; Ryan Peter L (BMC, 2011)
Abstract Background Relaxin hormone peptide is found in porcine follicular and utero-tubal fluids, but its possible actions during early embryo development are still undetermined. Here, we investigated the effects of porcine relaxin during oocyte maturation and embryo development, and gene expression in the pig. Methods Immature cumulus-oocyte complexes (COCs) were obtained from ovarian follicles of sows. In experiment 1, COCs were matured in the presence of 0, 20, or 40 ng relaxin/ml, or 10% (v/v) porcine follicular fluid. In experiment 2, COCs were in vitro matured, fertilized and resulting embryos were cultured in the presence of 0, 20, or 40 ng relaxin/ml. In experiment 3, COCs were matured in the presence of 40 ng relaxin/ml, fertilized and zygotes were cultured as indicated in experiment 2. We evaluated the proportions of matured oocytes in experiment 1, cleaved and blastocysts on Day 2 and Day 7 post insemination in all experiments. The total cell number of blastocysts was also evaluated. In parallel, transcription levels of both relaxin and its receptors (RXFP1 and RXFP2), as well as a pro- (Bax) and anti- (Bcl2-like 1) apoptotic-related genes were determined. All data were analyzed by ANOVA and significant differences were fixed for P < 0.05. Results In experiment 1, relaxin significantly increased the proportions of matured oocytes and cleaved embryos, as well as the expression level of RXFP2 mRNA compared to RXFP1 (P < 0.05). There was no effect on endogenous expression of relaxin and Bcl2-like1/Bax ratios. In all experiments, relaxin did not affect the proportions of blastocysts, but did significantly increase their total cell numbers (P < 0.05). Furthermore, no effect of relaxin was observed on Bcl2-like1/Bax expression ratios, which were similar between groups. Conclusions Exogenous relaxin influences its own receptors expression, improves oocyte nuclear maturation. Its beneficial effect on total cell number of blastocysts appears to be through a Bcl2-like1/Bax-independent mechanism.